Epimenides' midday sleep (Revista Archai, 2023)
From the scene of the singing cicadas in the Phaedrus, we will show the affinities between the mention of the dangerous sleep at noon (Phdr. 258e6-259d8) and a mythical episode in the life of Epimenides. Next, we will look at the possible affinities between the description of Dionysian madness (Phdr. 244d5-245a1) and the type of divination practiced by Epimenides of Crete (DK 3 B 1-25). From these approaches, we intend to describe and elucidate the common imaginary with which Plato elaborates his reception and assimilation of the archaic poetic tradition in his philosophy.